Evaluation and development of quality indices for adulteration in palm oil industry by used and recycled oils - Khor, Yih Phing (2019)
Currently, recycled oil has emerged as a prominent food safety issue and poses a major threat to the public health. Various studies have been conducted to detect the adulteration of used and recycled palm olein in refined, bleached, and deodorized palm olein (RBDPO). The presence of polymerized triacylglycerols (PTGs), monomeric oxidized triacylglycerols (oxTAGs), or caprylic acid (C8:0) has been proposed as a potential indicator to track the adulteration. Therefore, this study investigates the presence of these compounds in commercial cooking oils, their formation during various heating and deepfrying studies, and their presence in recycled oil samples. This study can be used to justify the suitability of these compounds for use as the quality indicators to trace the adulteration of used or recycled oil. In the first part of this study, a total of 23 commercial cooking oil samples were purchased from a market in Malaysia and were categorized into three main groups, namely, pure palm olein, blended palm olein, and packet oil. The total polar compounds (TPCs) for all fresh oil samples were within the safety limit for human consumption (< 25% polar compounds) set in many European countries. No triacylglycerol (TAG) oligomers, epoxy-, keto-, or hydroxy acids were detected in any of the fresh oil samples. In the second part of this study, a controlled heating study was carried out, RBDPO was heated continuously for 24 h at 160 °C, 170 °C, and 180 °C, with the oil sampled at 4- hour intervals. The oxTAG, TPC, and PTG concentrations in RBDPO increased significantly (p<0.05) with the temperature and heating time. At the end of the heating study, more epoxy acids were formed compared to keto and hydroxy acids. However, the TPC exceeded the limit of rejection for human consumption (>25% polar compounds). Moreover, caprylic acid, which was not present in fresh oil, was formed in significant amounts after the controlled heating study. In the third part of this work, two different types of food products, namely, sliced potato (SP) and chicken breast meat (CBM) were fried in a total duration of 200 min/day for seven consecutive days using RBDPO at 180 °C without any oil replenishment. The amounts of TPC, PTG, and caprylic acid that formed were significantly (p < 0.05) higher in the RBDPO used to fry SP compared to that used for CBM. The TPC in the RBDPO used to fry SP exceeded the limit of rejection for human consumption (> 25% polar compounds) on the seventh day of frying. In addition, the amounts of epoxy, keto, and hydroxy acids that formed were significantly (p < 0.05) higher in the RBDPO used to fry CBM compared to that used for SP. Following this, oil samples that underwent controlled heating and deep-frying studies were refined using the common oil refining procedure to simulate the production of recycled oil. PTG, TAG oligomers and dimers showed a significant increase (p < 0.05) after the refining process. The oxTAG, free fatty acid (FFA), peroxide value (PV), and p-anisidine value (AV) dropped significantly (p < 0.05) in the recycled RBDPO after the refining process. For the last part of the study, FT-NIR spectroscopy coupled with chemometrics was used to rapidly quantify the amount of thermo-oxidative products such as PTG, oxTAG, and TPC formed in used frying oil. Three separate partial least squares regression (PLS) models were built with high calibration accuracy. In conclusion, the few proposed potential quality indicators, namely PTG, oxTAG, and caprylic acid, were all detected in recycled oil. These findings justified the suitability of these parameters to be used in the quality indices to trace the adulteration of cooking oil as these compounds were not detected in the fresh oil. It is our hope that the findings of this study will be able to control the adulteration of used and recycled palm olein in RBDPO for the protection of the health and safety of consumers.